A Modified Self-Growing Rod Technique for Treatment of Early-Onset Scoliosis. Issue 3 (11th July 2022) - Mehdian, Hossein; Haddad, Sleiman; Pasku, Dritan; Masek, Craig; Nasto, Luigi Aurelio
Abstract : Background: Surgical treatment of early-onset scoliosis (EOS) remains challenging as no definitive surgical technique has emerged as the single best option in this varied patient population 1 -3 . Although the available surgical techniques may differ substantially, they all share the same goals of achieving and maintaining deformity correction, allowing physiological spinal growth, and reducing the number of operations and complications. Herein, we present a modified self-growing rod technique that represents a valid alternative to the existing surgical procedures for EOS. Description: The patient is positioned prone on a radiolucent table, and the spine is prepared and draped in a standard fashion. A posterior midline skin incision is made from the upper to the lower instrumented level. Subperiosteal exposure of the spine is carried out, ensuring that capsules of the facet joints are spared. Pedicle screws are inserted bilaterally at the cranial and caudal ends of the instrumentation. Fixation with pedicle screws of at least 3 levels at the top and bottom end is usually advised; in nonambulatory patients with pelvic obliquity, caudal fixation can be extended to the pelvis with bilateral iliac screws. Sublaminar wires are positioned bilaterally at every level between the cranial and caudal ends of the instrumentation and are passed as medially as possible to avoid damage to the facet joints. Four 5-mm cobalt-chromium rods are cut, contoured, and inserted at each end of the construct. Ipsilateral rods are secured with use of sublaminar wires, making sure that they overlap over a sufficient length to allow for the remaining spinal growth. Correction of the deformity is achieved with use of a combination of cantilever maneuvers and apical translation by progressive and sequential tightening of the sublaminar wires. The wound is closed in layers over a subfascial drain. The patient is allowed free mobilization after surgery. No postoperative brace is required. Alternatives: Nonoperative alternative treatment for EOS includes serial cast immobilization and bracing 4 . Alternative surgical treatments include traditional growing rods 5, magnetically controlled growing rods 6, the vertical expandable prosthetic titanium rib-expansion technique 7, and the Shilla technique 8 . The use of compression-based systems (i.e., staples or tether) 9 or early limited fusion has also been reported by other authors. Rationale: The main advantage of our technique is that it relies on physiological spinal growth and does not require surgery or external devices for rod lengthening, which is particularly beneficial in frail patients with a neuromuscular disease in whom repeated surgery is not advised. Segmental fixation by sublaminar wires allows good control of the deformity apex during growth. Concerns regarding early fusion of the spine have not been confirmed in our mid-term follow-up study 10 . Expected Outcomes: This technique allows correction of the deformity and continuous spinal growth in the years following surgery. At 6.0 years postoperatively, the average main curve correction was reported to be 61% and the average pelvic obliquity correction was 69%. The spine was reported to lengthen an average of 40.9 mm (range, 14.0 to 84.0 mm) immediately postoperatively, and the T1-S1 segment was reported to continue growing at 10.5 mm/year (range, 3.6 to 16.5 mm/year) thereafter 10 . The most common complication is rod breakage at the thoracolumbar junction, which seems to be more common in patients with idiopathic or cerebral palsy EOS and during the pubertal growth spurt 10 . Important Tips: Subperiosteal exposure of the spine should be carried out, making sure to preserve facet joints in the unfused area of the spine. Achieve segmental fixation with use of sublaminar wires at every level and pedicle screws at the top and bottom ends of the instrumentation. If pelvic imbalance is present and the patient is nonambulatory, pelvic fixation with iliac screws is advised. First round correction of the deformity is achieved with a cantilever technique; correction fine-tuning can be performed by tightening sublaminar wires. Consider utilizing thicker rods in cases of idiopathic or cerebral palsy EOS. Acronyms and Abbreviations: EOS = early-onset scoliosis AP = anteroposterior EV = end vertebra SSEP = somatosensory evoked potentials MEP = motor evoked potentials PJK = proximal junctional kyphosis SMA = spinal muscular atrophy CP = cerebral palsy PACU = post-anesthesia care unit